SIGNIFICANCE OF BLEEDING DURING ACUTE PULMONARY EMBOLISM TREATMENT - Subotić Atanasković, Bojana; Obradović, Slobodan (Medicinski podmladak, 2024)
Anticoagulant drugs are basic therapy for all the patients in whom pulmonary embolism (PE) is highly suspected or diagnosed. It must be initiated as soon as PE diagnose is established and its duration of at least three months is recommended. In patients with the worst hemodynamic status, concomitant thrombolytic therapy is recommended, for immediate lung reperfusion and to reduce mortality. Both anticoagulant and thrombolytic therapy carry increased risk for bleeding, which increases morbidity, contributes to treatment modification and also could be fatal. Therefore, individual bleeding risk assessment is neccessary during PE management, and risk minimization strategies should be employed whenever is possible. Beside common bleeding risk factors, few predictive models were formed. In PE population treated with thrombolysis two-leveled PEBSI score has been derived, but the an external validation is needed.  During stable, long-term oral anticoagulant therapy, VTE-BLEED score showed high predictive value for bleeding event even in the external PE population. In order to minimize bleeding risk, new generation drugs are recommended (tissue plasminogen activator over streptikinase and urokinase; low molecular weight heparins or fondaparinux over unfractionated heparin (UFH); novel oral anticoagulants (NOACs) over vitamine K antagonist (VKA) drugs), as well as dose adjustment to renal function and drug activity biomarkers (activated partial thromboplastic time for UFH, or international normalized ratio for VKAs). It is still unclear whether reduced dose of thrombolytics has safer profile then full therapeutic doses. In PE patients with high risk for hemorrhage who need aggressive tretment, surgical thrombectomy or percutaneous interventions should be considered, although their availability is restricted to small number of centres.
Keywords: pulmonary embolism, bleeding, score, minimize risk